Death Anxiety and Life Expectancy among Older Adults in Iran - Vahid Rashedi; Banafsheh Ebrahimi; Mahtab Sharif Mohseni; Mohammadali Hosseini (Journal of Caring Sciences, 2020)
Introduction: Life expectancy is one of the indices used to analyze health status. This index changes during aging as a result of a variety of incidents, diseases, stress, and anxiety. Death anxiety is one of the problems that can turn into a deadly fear. This study was aimed to determine the association between life expectancy and death anxiety among older adults in Tehran, Iran. Methods: In this correlational descriptive study, 208 older adults aged ≥ 60 years, who had referred to adult daycare centers in Tehran, were chosen by cluster random sampling. Data were collected using a demographic questionnaire, Temper’s death anxiety scale and Snyder's life expectancy scale. Data analysis was completed through SPSS ver. 22. Results: The mean age of the older adults was 66.60 (6.58) years. The results showed a mean death anxiety of 12.21 mean life expectancy of 24.94. Furthermore, Pearson’s correlation coefficient indicated a negative correlation between death anxiety and life expectancy. The results of multiple regression analysis revealed that the major predictor of life expectancy decline were death anxiety, age, and residential status. Conclusion: It can be concluded from the results that the negative correlation between death anxiety and life expectancy requires teaching coping methods for anxiety and using appropriate methods to improve life expectancy among older adults.